Mentoring in international assignments: a personality traits perspective. Issue 7 (6th November 2017) - Schuster, Tassilo; Ambrosius, Judith; Bader, Benjamin
Abstract : Purpose: The purpose of this paper is to analyze the impact of personality and mentorship on expatriates' psychological well-being. The authors argue that certain personality traits (extraversion, agreeableness, conscientiousness, emotional stability, and openness to experience) have positive effects on expatriates' psychological well-being and that these personality traits enable them to derive a greater benefit from mentorship. By doing so, this study identifies for which personality traits which type of mentoring (home or host country mentor) is most beneficial. Design/methodology/approach: Based on socioanalytic theory, the authors develop theory-driven hypotheses and test them against data of 334 expatriates. Findings: The study shows that several personality traits as well as home country mentorship have a significant positive impact on psychological well-being, whereas host country mentorship shows no significant positive effects. Moreover, the study indicates that home and host country mentorship partially moderates the relationship between personality traits and psychological well-being. Originality/value: Since the authors derive important implications for the selection process of expatriates as well as for the implementation of mentoring in multinational corporations, this study is of value for researchers and practitioners in the areas of human resource management and organizational studies.